2020
DOI: 10.1016/j.conbuildmat.2020.120078
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of rheological parameters, induced bleeding, permeability and mechanical properties of supersulfated cement grouts

Abstract: Presenting a promising option that could be used to encapsulate nuclear waste material for disposal, supersulfated cement (SSC) is, again, receiving wide attention among research community as a cementitious system that has noteworthy properties. It is also an environmentally friendly cement since it is mainly composed of ground granulated blast furnace slag (GGBS) that is activated by a sulphate source such as gypsum, hemihydrate or anhydrite. Although there is some research on SSC, little research work has fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The viscosity of the grout with w/b = 0.46 (G2 and G4) is lower than the grout with w/b = 0.39 (G1 and G3). As expected, the increase of water reduces the viscosity due to the reduction of interparticle forces [16,17].…”
Section: Rheological Measurementssupporting
confidence: 73%
“…The viscosity of the grout with w/b = 0.46 (G2 and G4) is lower than the grout with w/b = 0.39 (G1 and G3). As expected, the increase of water reduces the viscosity due to the reduction of interparticle forces [16,17].…”
Section: Rheological Measurementssupporting
confidence: 73%
“…It is well-known that the as a mathematical and statistical approach, response surface methodology (RSM) has been widely applied to investigate the influence of independent variables and the interaction among those independent variables, which has demonstrated a great potential for experimental optimisation, particularly in optimising the rheological parameters, hydration and mechanical properties of cementitious materials [35][36][37][38]. Among different RSM approaches, Box-Behnken design (BBD), a rotatable second-order design developed from the three-level factorial design, is often used as a tool for investigation of the influence of variables, in particular, the cases with interactions among variables, due to fewer testing requirements, which has been applied in cement and concrete research [39].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the RSM jointly used with the statistic design method (e.g., CCD) is recognised as a significant approach in the design and optimisation process, which has also recently been effectively employed to investigate the interactive effects of independent variables in many areas [ 24 , 25 , 26 ]. In the field of cement and concrete research, RSM demonstrated great potential for experimental optimisation, particularly in optimising the rheological parameters, hydration and mechanical properties of cementitious materials [ 27 , 28 , 29 , 30 ]. Recently, Hou et al [ 31 ] presented their research on optimising the setting time and early-age compressive strength of MPC cement with RSM methodology for rapid repair applications.…”
Section: Introductionmentioning
confidence: 99%